The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1136/vr.96.9.194
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into diagnosis and treatment of cobalt deficiency in lambs

Abstract: The development of cobalt deficiency was studied in 30 Scottish Blackface lambs grazing pasture on a soil containing 0-17 ppm cobalt. By the end of an eight-week period 50 per cent of lambs were subjectively appraised as showing signs of cobalt deficiency. After a further period lasting four weeks, during which three groups of lambs were studied (one group, least affected by cobalt deficiency, acted as control, the second received a single cobalt bullet and the third received oral doses of 200 mg cobalt chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The non-supplemented lambs always had serum vitamin B12 concentrations around or below 200 pmo1/1 at the start of the experimental periods and these values dropped to below 100 pmo1/1 during the experiments. Suttle (20) suggested that a serum vitamin B12 concentration of 188 pmo1/1 is probably the threshold between marginal and functional deficiency, while others indicate the margin to be between 150 and 300 pmo1/1 (2,6,7,9,16,21,22). This indicates that the non-supplemented lambs were B12 deficient shortly after the start of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The non-supplemented lambs always had serum vitamin B12 concentrations around or below 200 pmo1/1 at the start of the experimental periods and these values dropped to below 100 pmo1/1 during the experiments. Suttle (20) suggested that a serum vitamin B12 concentration of 188 pmo1/1 is probably the threshold between marginal and functional deficiency, while others indicate the margin to be between 150 and 300 pmo1/1 (2,6,7,9,16,21,22). This indicates that the non-supplemented lambs were B12 deficient shortly after the start of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The third approach, adopted by many groups, has been to measure either plasma concentrations of methylmalonic acid (MMA), as a diagnostic marker of Co-deficiency (O'Harte et al 1989), or tissue concentrations of MMA as an alternative indicator of the functional status of the mutase enzyme (Smith et al 1969). Similarly, formininoglutamic acid (FIGLU) concentrations in plasma have been measured as markers of the functional status of the synthetase enzyme (Russel et al 1975). However, unlike MMA, which has now gained widespread acceptance as a diagnostic marker, the use of FIGLU is not common, probably as the result of the unreliability of its assay (Stebbings & Lewis, 1986).…”
Section: G K E N N E D Y a N D Othersmentioning
confidence: 99%
“…Despite these difficulties in interpreting serum cobalamin data, the approach has proved reasonably satisfactory for discriminating between normal and severely Co-deficient sheep on the basis of threshold cobalamin values of approximately 200 to 300 ~g cobalamin/ liter serum (Russel et al, 1975). It is proving less satisfactory for the diagnosis of a mild Co deficiency.…”
Section: Metabolic Indices Of Cobalt Deficiencymentioning
confidence: 99%